2021
DOI: 10.18261/issn.2387-5984-2021-03-04
|View full text |Cite
|
Sign up to set email alerts
|

Palliasjon og lindring – en begrepsbestemmelse ved bruk av etymologiske ordbøker og offentlige dokumenter

Abstract: Palliasjon er et begrep som har fått økende aktualitet de senere årene. Betegnelsene palliasjon og lindring anvendes ofte i norske fagmiljøer. Imidlertid er det knyttet uklarhet til begrepene og bruken av dem i klinisk praksis. Hensikten med studien er å klargjøre begrepene palliasjon og lindring og derigjennom skape en dypere forståelse for dem.Vi foretok en analyse av begrepene palliasjon og lindring ved bruk av etymologiske ordbøker. Den kontekstuelle bestemmelsen tok utgangspunkt i norske offentlige dokume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Applequist and Daly [ 20 ] found that the concepts of palliation and PC have several similarities, but while PC involves provision of physical, emotional, psychological and social care, palliation is a patient-centred outcome, such as symptom relief by means of a noncurative intervention and human presence. One study found that palliation and alleviation are not synonymous concepts but that they are complementary [ 23 ]. HCPs describe the term PC as a blurred and confusing concept that is associated with end-of-life care [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Applequist and Daly [ 20 ] found that the concepts of palliation and PC have several similarities, but while PC involves provision of physical, emotional, psychological and social care, palliation is a patient-centred outcome, such as symptom relief by means of a noncurative intervention and human presence. One study found that palliation and alleviation are not synonymous concepts but that they are complementary [ 23 ]. HCPs describe the term PC as a blurred and confusing concept that is associated with end-of-life care [ 24 ].…”
Section: Introductionmentioning
confidence: 99%